2020
DOI: 10.3390/lubricants8020016
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Based Modelling of Adhesive Wear in the Mixed Lubrication Regime

Abstract: Adhesive wear in dry contacts is often described using the Archard or Fleischer model. Both provide equations for the determination of a wear volume, taking the load, the sliding path and a set of material parameters into account. While the Fleischer model is based on energetic approaches, the Archard formulation uses an empirical factor—the wear coefficient—describing the intensity of wear. Today, a numerical determination of the wear coefficient is already possible and both approaches can be deduced to a loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Thereby, wear was higher in the area of the negative slip. This stands in good agreement with the experimental results from Terwey et al [13,14]. Despite differences in absolute values due to the less severe conditions (lower loads and higher velocities) and the operation being in the mixed instead of the boundary lubrication regime, the qualitative profiles agree well.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Thereby, wear was higher in the area of the negative slip. This stands in good agreement with the experimental results from Terwey et al [13,14]. Despite differences in absolute values due to the less severe conditions (lower loads and higher velocities) and the operation being in the mixed instead of the boundary lubrication regime, the qualitative profiles agree well.…”
Section: Resultssupporting
confidence: 90%
“…Sfantos et al [12] suggested a boundary element formulation for three-dimensional dry sliding wear based on Archard's model, which was applied to a pin-on-disc contact as well as to a hip arthroplasty wear problem. As aforementioned approaches did not take deterministic surface topography into account, Terwey et al [13,14] implemented a contact and wear model based upon the half-space theory for boundary lubricated thrust roller bearings, considering surface roughness. Thereby, the wear coefficient of Archard's law was determined using continuum damage mechanics (CDM).…”
Section: Of 21mentioning
confidence: 99%
“…For example, most studies ignored the force balance at the interface of the three bodies, or only discussed the dry abrasive wear of the three bodies [20][21][22][23]. Without considering the effect of the third body on the 2-body lubrication wear [24,25], resulting in assumptions about the load-sharing ratio of the liquid, surface and particle load are different from the actual load for the three bodies. The relationship between the real contact area and the separation between interfaces (considering different average third body diameter and equivalent surface RMS roughness) has not been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Wear predictions based on frictional energy dissipation were performed for fretting wear [419,420]. Terwey et al [421] compared the adhesive wear in dry and mixed lubrication between the Archard's equation and an energy-based model, and they concluded that determining a critical number of load cycles for each asperity, a local wear coefficient, and local wear depth can be calculated with the energy-based model. According to the theory of Kragelskii, adhesive wear rate can be estimated by using a friction fatigue failure equation of asperities.…”
Section: Numerical Predictions Of Wear Profile and Wear Ratementioning
confidence: 99%